The Go-Between: Augustine on Deacons - Koet, Bart. (Brill's Studies in Catholic Theology, 2019)
In recent and contemporary scholarship, the deacon as a leader in the Early Church is an often-neglected subject. This book focuses on the roles and functions of the deacon in Augustine's literary output. The author's approach is detailed and appropriately cautious and is always attentive to the text. He analyses Augustine's way of commenting on deacons and how the bishop of Hippo wrote about them, as well as his manner of preaching on saints and martyrs who were deacons. The book thus provides a new perspective on the early deacons who were not social workers, but go-betweens or intermediaries between the bishop and his flock, between the Scriptures and daily life, and between Church and society. He emphasises in particular how deacons were epistle bearers responsible for the world wide web of Early Christianity.